Social and emotional learning - Portuguese and Spanish teachers’ representations and classroom practices - Ferreira, Marco; Reis-Jorge, José; Olcina-Sempere, Gustau (Frontiers in Education, 2025)
IntroductionThis study aims to uncover the representations and practices of Portuguese and Spanish school teachers regarding social and emotional learning (SEL), hoping to contribute to filling a perceived gap in the empirical literature of these two countries.MethodsThis is an exploratory qualitative study with a convenience sample of 68 Portuguese and Spanish teachers who responded to an open-ended questionnaire. The teachers’ responses were analyzed following a hybrid approach to the method of thematic analysis. As an extension to the study, we checked the level of similarity of the perspectives and practices expressed by the Portuguese and the Spanish teachers.ResultsThe findings reveal the participants’ awareness of the theoretical foundations of SEL with an emphasis on the association between SEL and students’ mental health. In terms of classroom practices, they tended to implement activities involving students in reflecting on their feelings and emotions to facilitate the development of healthy social and emotional behavior. No significant differences were found between teachers from the two countries.DiscussionOur findings echo previous research showing that teaching SEL cannot be a process carried out haphazardly or intuitively. Teachers who are well-trained and prepared to teach are more willing to change their practices and more likely to implement SEL in their classrooms. Therefore, the development of teaching skills in SEL should be part of initial and in-service teacher training programs to become competent in promoting a whole school approach.